Study of proprioceptive function in professional volleyball athletes with atrophy of the infraspinatus. Issue 6 (10th April 2011) - Salles, J I; Alves, H; Amaral, M V; Cagy, M; Cunha-Cruz, V; Piedade, R; Ribeiro, P
Abstract : Background: The isolated atrophy of the infraspinatus muscle is an uncommon clinical alteration, generally secondary to the selective lesion of the suprascapular nerve related to sport activities, especially in professional volleyball players. The lesion of the suprascapular nerve can cause kinesthetic deficits. The assessment of kinesthesia is determined by the ability to detect joint movement and has been traditionally conducted by measuring the Threshold of Perception of Passive Motion (TPPM). Objective: The goal of the present study was to compare the TPPM among a group of healthy individuals (control group), a group of World League volleyball players with atrophy of the infraspinatus muscle on the dominant side, and group of athletes with no shoulder pathologies. Design, setting and participants: Observational study at a controlled research laboratory at the Brazilian Volleyball Training Center (CDV – Saquarema). 12 healthy non-athlete controls, 12 athletes with atrophy of the infraspinatus muscle, and 12 athletes without the atrophy. Interventions: A proprioception-testing device passively moved the shoulder and participants were instructed to respond as soon as movement was detected (TPPM) by pressing a button-switch. EEG and electromyographic (EMG) activities were recorded simultaneously. Response latency was established as the delay between the stimulus (movement) and the response (button press). The time-frequency dynamics of the EEG was analyzed. Results: An analysis of variance indicated a significant latency reduction (p<0.000) in the group of athletes without the atrophy when compared both to the group of athletes with the atrophy and to the control group. Furthermore, distinct patterns of cortical activity were observed in the three experimental groups. Conclusions: The results suggest that systematically trained motor abilities, as well as the atrophy of the infraspinatus muscle, change the cortical representation of the different stages of proprioceptive information processing and, ultimately, the cortical representation of the TPPM.